Synthesis and In Vitro Cytotoxic Activity of Chromenopyridones. (8th January 2012) - Singh, Balwinder; Sharma, Vishal; Singh, Gagandeep; Kumar, Rakesh; Arora, Saroj; Ishar, Mohan Paul Singh
Abstract : Novel substituted chromenopyridones (3a –j and6a –d ) were synthesized and evaluated in vitro for the cytotoxic activity against various human cancer cell lines such as prostate (PC-3), breast (MCF-7), CNS (IMR-32), cervix (Hela), and liver (Hep-G2). preliminary cytotoxic screening showed that all the compounds possess a good to moderate inhibitory activity against various cancer cell lines. Particularly, compound6b bearing allyl moiety displayed a significant cytotoxic potential in comparison to standard drugs.